Trust, risk and public key infrastructure model on e-procurement adoption - Nanang, Herlino; Misman, Ahmad Fatzilah; Zulkifli, Zahidah (IEEE, 2017)
It is inevitable that the use of information and communication technologies (ICT) has been widespread in various sectors, including the governmental sectors. The implementation has brought many benefits, especially to improve performance of the public services. This is a strong reason for developing countries to encourage ICT utilizations, like Indonesia. One of the technological implementations is procurement system, which has been implemented by the Indonesia government. Despite the fact that, the electronic procurement (e-procurement) system has been implemented for nearly one decades, there are studies in this system implementation. The findings of the previous tend to present the incomplete understanding of the system implementation. In addition, further studies around the E-Procurement are still needed to be conducted, in order to examine the factors that influence the system implementation. The researcher adopt research model related with trust, and public key infrastructure constructs. The expectation is a comprehensive finding of the factors locally into the process of government procurement